CLASSROOM DESIGN IN THE IMPLEMENTATION OF DEEP LEARNING AT SD NEGERI 16 BANDA ACEH - Baiti Nurhidayah; Sri Rahmi (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze classroom design in supporting the implementation of deep learning in primary education, with a case study conducted at SD Negeri 16 Banda Aceh, Indonesia. The research is grounded in the implementation of the Merdeka Curriculum, which emphasizes meaningful, student-centered, and in-depth learning, where the physical learning environment functions as a silent curriculum shaping student interaction and engagement. A qualitative descriptive approach was employed, with data collected through classroom observations, in-depth interviews with teachers and the school principal, and document analysis. The findings indicate that classroom design in the school is flexible and adaptive, utilizing various seating arrangements such as traditional, U-shaped, cluster-based, and modified V-shaped formations aligned with instructional objectives. These spatial arrangements were found to enhance active participation, collaboration, and students